Occupational asthma caused by bacillary amylase used in the detergent industry. Issue 12 (1st December 2000) - Hole, A M; Draper, A; Jolliffe, G; Cullinan, P; Jones, M; Taylor, A J Newman
Abstract : Four cases are reported of occupational asthma due to amylase derived from Bacillus licheniformis, used in detergent washing powders. It is thought that these are the first reported cases of asthma due to this enzyme in the detergent industry. All four employees (men) were from the same factory and none had a history of asthma or atopy. All developed symptoms of wheeze at work after an initial symptom free period. Symptoms improved during periods away from work. All undertook serial peak flow recordings (not diagnostic) and underwent skin prick tests, radio allergosorbent test (RAST) measurement, and specific bronchial provocation testing. The bronchial provocation testing was performed by a dust tipping method in a single blind manner, with lactose as an inert control and powdered amylase, provided by the employer, as an active agent. Serial measurements of forced expiratory volume in 1 second (FEV1 ) were recorded and histamine provocative concentration causing a 20% fall in FEV1 (PC20 ) tests were determined before and 24 hours after each challenge. Patient 1 developed an isolated early reaction, patient 2 an isolated late reaction, and patients 3 and 4 developed dual reactions. All showed an increased non-specific bronchial responsiveness after active challenge. The introduction of encapsulated enzymes in the detergent industry was followed by a reduction in the incidence of respiratory sensitisation. These patients developed occupational asthma despite working only with encapsulated enzymes. This highlights the importance of careful surveillance after the introduction of new agents in the workplace.